Conflict-free four-dimensional path planning for urban air mobility considering airspace occupancy - Dai, Wei (2021)
Urban air mobility (UAM) has attracted the attention of aircraft manufacturers, air navigation service providers and governments in recent years. Preventing the conflict among urban aircraft is crucial to UAM traffic safety, which is a key in enabling large scale UAM operation. Pre-flight conflict-free path planning can provide a strategic layer in the maintenance of safety performance, thus becomes an important element in UAM. This paper aims at tackling conflict-free path planning problem for UAM operation with a consideration of four-dimensional airspace management. In the paper, we first introduce AirMatrix, previously developed by the team, and extend it as a four-dimensional airspace management concept. On the basis of AirMatrix, we formulate the shortest flight time path planning problem considering resolution of conflicts with both static and dynamic obstacles. A Conflict-Free A* (CFA*) algorithm is developed for planning four-dimensional paths based on first-come-first-served scheme. The algorithm contains a novel design of heuristic function as well as a conflict detection and resolution strategy. Numerical simulation was carried out using the building information in a typical urban area in Singapore. The results show that the algorithm can generate paths resolving a significant number of potential conflicts in airspace utilization, with acceptable computational time and flight delay. The findings of this study will provide references for stakeholders to support the development of UAM.